Evaluation of two rapid commercial assays for detection of Streptococcus agalactiae from vaginal samples - Hendrik Koliwer‐Brandl; Ahmed Nil; Jana Birri; Maike Sachs; Roland Zimmermann; Reinhard Zbinden; Dalia Balsyte (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Streptococcus agalactiae, also known as group B streptococci (GBS), is associated with invasive infections in neonates. Identification of GBS vaginal colonization in pregnant women before delivery is essential for treatment with antibiotics to prevent intrapartum vertical transmission to the newborn. This study was designed to evaluate applicability of two rapid real‐time PCRs in comparison to standard culture identification. Material and methods We compared the Xpert GBS assay, hereafter referred to as Xpert, and GenomEra GBS PCR, hereafter referred to as GenomEra. The standard culture identification consisted of two different agar plates as well as an enrichment broth. Results We analyzed vaginal samples of 260 pregnant women; 42 samples were tested GBS‐positive by using standard culture as a gold standard, 30 by Xpert, and 37 by GenomEra. Xpert and GenomEra assays performed with sensitivities of 71.4% and 88.1% as well as specificities of 98.6% and 99.1%, respectively. Twelve vaginal samples were false‐negative by Xpert and five samples by GenomEra. Interestingly, three negative Xpert results of standard culture‐positive samples exhibited high Ct‐values indicating the presence of GBS. If higher Ct‐values are taken into consideration, the sensitivity of Xpert increases up to 78.6%. Moreover, only three Xpert PCRs had to be repeated, whereas two Genomera were invalid even after repetition and further 15 GenomEra PCRs were repeated because of borderline results or inhibition of the PCR test. Conclusions In this study, GenomEra assay performed with a higher sensitivity than the Xpert PCR. On the other hand, the Xpert assay needs less hands‐on‐time for a sample preparation and requires approximately four‐fold less repetitions as compared to the GenomEra assay. This robust performance of the Xpert assay make it applicable as a rapid intrapartum point‐of‐care test, although a higher sensitivity would be desirable. Therefore, culture in the 35–37 week of gestation remains the gold standard to detect vaginal colonization.